Design of Cognitive Conflict-Based Generative Learning LKPD on Measurement Material to Improve Creative Thinking Ability of Class X High School Learners - Fitri, Hidayatul; Akmam, Akmam; Ratnawulan, Ratnawulan; Suherman, Dea Stivani (Physics Learning and Education, 2025)
Education and learning play an important role in developing individual character and skills. Learning is a process that is specifically designed to help individuals develop their thinking skills. Learning models can be an effective tool to achieve optimal learning. LKPD will certainly be more effective with the help of learning models in improving student learning outcomes. The problem found is that the use of LKPD in learning has not helped students to construct new knowledge with old knowledge they already have, the learning model is not optimal for building new knowledge of students and students' creative thinking skills are still relatively low. This research aims to develop a valid and practical cognitive conflict-based generative learning LKPD. This research uses the Research and Development (R&D) method with the 4D development model (define, design, develop, disseminate). The define stage includes needs analysis and problem identification. At the design stage, the LKPD was designed by considering the content, structure, and aesthetic components. The develop stage involves validity testing by experts, as well as practicality testing by practitioners and users. Based on the validation and practicality instruments that have been analyzed, it can be concluded that the LKPD for cognitive conflict-based learning on measurement material produced is valid with Aiken's V of (0.9) with a valid category. While the practicality of educators and students is obtained at (90.1) and (90.4) with a very practical category.